Coping strategies for Kirkuk University students (Journal of Humanities and Social Sciences Research, 2023)
Management strategies of Kirkuk university students.-Differences with statical significance for management strategies according to gender(female ,male),specialization(scientific, human)and stage(first ,fourth).in order to achieve the objectives of the research ,the researcher prepared scale (consideration strategies) ,which consisted of (41)items and for each paragraph (5)calmatives are (5)are (  I have always done this ,I have done this often, I have done this sometimes ,I have done this rarely ,and the never do this.Psychometric properties of the scale have been extracted from discrimination and validity of its logical and apparent types and constructivist, and as for the stabilities was extracted by re-testing, where the number reached (0,81) and Cronbach’s alpha coefficient, which reached number (0,83).